Geological interpretation of volcanism and segmentation of the Mariana back‐arc spreading center between 12.7°N and 18.3°N. (23rd June 2017) - Anderson, Melissa O.; Chadwick, William W.; Hannington, Mark D.; Merle, Susan G.; Resing, Joseph A.; Baker, Edward T.; Butterfield, David A.; Walker, Sharon L.; Augustin, Nico
Abstract: The relationships between tectonic processes, magmatism, and hydrothermal venting along ∼600 km of the slow‐spreading Mariana back‐arc between 12.7°N and 18.3°N reveal a number of similarities and differences compared to slow‐spreading mid‐ocean ridges. Analysis of the volcanic geomorphology and structure highlights the complexity of the back‐arc spreading center. Here, ridge segmentation is controlled by large‐scale basement structures that appear to predate back‐arc rifting. These structures also control the orientation of the chains of cross‐arc volcanoes that characterize this region. Segment‐scale faulting is oriented perpendicular to the spreading direction, allowing precise spreading directions to be determined. Four morphologically distinct segment types are identified: dominantly magmatic segments (Type I); magmatic segments currently undergoing tectonic extension (Type II); dominantly tectonic segments (Type III); and tectonic segments currently undergoing magmatic extension (Type IV). Variations in axial morphology (including eruption styles, neovolcanic eruption volumes, and faulting) reflect magma supply, which is locally enhanced by cross‐arc volcanism associated with N‐S compression along the 16.5°N and 17.0°N segments. In contrast, cross‐arc seismicity is associated with N‐S extension and increased faulting along the 14.5°N segment, with structures that are interpreted to be oceanic core complexes—the first with high‐resolution bathymetry described in an active back‐arc basin. Hydrothermal venting associated with recent magmatism has been discovered along all segment types. Key Points: Ridge segmentation is controlled by preexisting basement structures Spreading is perpendicular to the back‐arc axis, allowing precise spreading directions to be determined Segment morphology reflects magma supply, which is locally enhanced by proximity to cross‐arc volcanoes